The Concept Of Crime Organized Crime: Problems and Proposals (2016)
This paper delves into the understanding of the transnational organized crime concept, given the lack of agreement on its content and deficiency of regulation. It is a typical concept of the complexity of postmodernism; therefore it presupposes previous c